Some e-Learning Tools for Knowledge-based Society - Paragină, Florica; Paragină, Silviu; Jipa, Alexandru (Journal of Research in Educational Sciences; Vol 1 No 2 (2010): JRES, Volume I, Issue 2(2), Winter 2010, 2010)
Now, there are developed many e-Learning platforms, but, this system is at the beginning, yet. Till now, a lot of methodological and didactical compounds were developed similar with the classical system of education. The utilisation of an e-Learning platform is not easy for all and there are big differences of the results obtained in this kind of education system, between the young students and the older one. Many universities developed their own e-Learning system but they had to surpass a lot of problems due to the technical requirements for the server and, also, for the software used for providing the students access into system. The introduction of the SCORM requirements had provided a modality for measurement of the education’s quality obtained using this kind of education at distance. Another problem was to ensure a personalized access to the platform, for every student, 24 h per day and 7 days per week and also for a large number of students. But, now, this was resolved due to technical innovation in the computers manufacturing process. From our point of view, the payment for the stuff involved in this kind of education is not yet very well defined. In this paper, we shall present our experiences as students and as non-editing teacher in using MOODLE platform and the second Life Environment, compared with the traditional education systems for students and adult persons. We are not able to identify a general perception of the e-Learning Education System, because its evaluation differs in function of the age of the teachers, students involve or not in this kind of education, and of the mass-media representative or of the researchers in education who develop studies in this field.